Endoscopic band ligation versus argon plasma coagulation in the treatment of gastric antral vascular ectasia: systematic review and meta-analysis - Garg, Archit; Moond, Vishali; Bidani, Khyati; Garg, Aashi; Broder, Arkady; Mohan, Babu P.; Adler, Douglas G. (Gastrointestinal endoscopy, 2025)
Argon plasma coagulation (APC) is the established endoscopic treatment for gastric antral vascular ectasia (GAVE). Recently, the use of endoscopic band ligation (EBL) has gained recognition as an alternate approach. The objective of our study was to compare the efficacy and safety of APC versus EBL in the treatment of GAVE. Multiple databases were searched for articles on APC versus EBL for GAVE treatment. Preferred outcomes were subjected to systematic review and meta-analysis. We analyzed 10 studies involving 476 subjects (47.47% men and mean age of 56.25 years). The number of sessions required for the obliteration of lesions was higher with APC. The pooled eradication rate of GAVE with EBL was 88.6% (95% CI, 79.9-81.5; I2 = 13.5%) and with APC was 57.9% (95% CI, 43.7-71; I2 = 59%; relative risk [RR], 1.52; 95% CI, 1.16-2.02; I2 = 72%; P < .001). EBL had a lower bleeding recurrence (6.6%; 95% CI, 3.4-12.5; I2 = 0%) compared with APC (39.7%, 95% CI, 26.9-54.15; I2 = 55%; RR, 0.21; 95% CI, 0.09-0.44; I2 = 0%; P < .001). GAVE recurrence with EBL was 7.3% (95% CI, 3.8-13.6; I2 = 0%) and with APC was 38.5% (95% CI, 24.4-54.9; I2 = 64%; RR, 0.22; 95% CI, 0.109-0.446; I2 = 0%; P < .01). Transfusion requirements and hospitalizations were lower with EBL compared with APC. Adverse events associated with EBL were 16.8% (95% CI, 6.6-36.7; I2 = 83%) compared with APC at 9.3% (95% CI, 5.6-15.1; I2 = 19%; RR, 2.11; 95% CI, 0.8-5.46; I2 = 58%; P = .1). EBL demonstrated better eradication with fewer treatment sessions, recurrent bleeding, hospitalizations, and transfusion requirements as compared with APC. It is time that EBL be used as the first-line endoscopic treatment for GAVE. [Display omitted]